Προσομοίωση καθοδικής προστασίας πλωτής υπεράκτιας κατασκευής πολλαπλών χρήσεων - Γιαννίκιος, Ιωάννης (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών. Τομέας Θαλάσσιων Κατασκευών, 2018)
This thesis investigates the cathodic corrosion protection system of a multipurpose floating structure by developing a model (FEM – in Comsol Multiphysics) and applying simulations on the designed floating structure. A Corrosion model for GACP (Galvanic Anode Cathodic Protection) systems is developed which considers seawater conductivity, anodes capacity, environmental conditions and predicts the steel’s potential and current flow. Kinetic expressions, as simulation input, are iteratively fitted to measured potentials until the simulation outcomes match desired potential and current values. The calculated average and maximum protection potential at the structure’s surface is calculated and compared to the requirements that classification society dictates, namely DNV-GL. Salt water and humidity increase corrosion rate on intermittently or completely submerged parts of the structure. But high levels of corrosion decrease the bearable loads by reducing the components’ dimensions and therefore increasing the resolved stress and strain. Hence, it is obligatory to evaluate the corrosion rate and evolution during the structure’s service life and if it is effectively protected against corrosion. To prevent thickness reduction beyond the allowed margins on the structural components, certain regulations instructed from DNV have to be met regarding the potential distribution and the dissolution (thus current) of the structure and the protection system. However, the corrosion rates will vary within the different components of the marine structure, depending on their position relative to the protection means, but also to the state of the protection system (e.g. the current provided in a certain component will be less if the same source sends current to another one). It is therefore necessary to apply calculations on each floating structure before the anodes are installed (especially when new design is made). The examined structure is a result of the thorough research conducted by the Laboratory for Floating Structures and Mooring Systems of National Technical University of Athens. Moreover, it is a multi-purpose floating structure suitable for offshore wind and wave energy sources exploitation. This structure has not been installed yet and the study of the cathodic protection system is vital since its design is groundbreaking and one of the kind. This study showed that the solely use of a GACP system is insufficient to meet the DNV-GL standards and a combination of anti-corrosive methods is needed. In detail, because of the complexity of the platform’s geometry the anodes were incapable to keep the potential below -0.9 Volts (as the classification society dictates) on the surface of the steel structure. As a result the steel’s degradation would initiate at 17 years while at -0.8Volt and will result a loss of 0.4 mm in thickness for some parts of the platform by the end of the design life. Consequently, an alternative of applying cathodic protection by means of GACP combined with the use of coatings on the endangered surfaces has been introduced. In this case the DNV-GL standards were successfully met and the service life of the structure was eventually prolonged to 25 years.